Impact of Dark Triad on Anxiety Disorder: Parallel Mediation Analysis During Pandemic - Shengbo, Liu; Fiaz, Muhammad; Mughal, Yasir H.; Wisetsri, Worakamol; Ullah, Irfan; Ren, Diandian; Kiran, Alina; Kumar Kesari, Kavindra (Frontiers in Psychology, 2022)
The current study aimed to investigate the mediating role of loneliness, ASMR, on the relationship between narcissism, Machiavellianism, and psychopathy and anxiety disorder. The population of the study was professionals working in public and private sector organizations. Non-probability snowball technique was used. Data was collected from 512 professionals. Total 653 questionnaires were distributed and 512 were used in the analysis yielding a response rate of 78.4%. PLS-SEM was used to analyze the data. Measurement and structural models were developed to test the reliability, validity of the scales as well as hypotheses. Findings of the measurement model revealed that scales were reliable and valid while results of the structural model revealed that narcissism, psychopathy, Covid loneliness, and ASMR have a significant direct impact on anxiety disorder but Machiavellianism does not have a significant effect on anxiety disorder. In addition, Covid loneliness and ASMR mediated between narcissism and psychopathy but does not significantly mediate between Machiavellianism and anxiety disorder. The current study has extended the body of knowledge by bridging the two theories theory of attachment and cognitive dissonance theory. The current study has provided the primary evidence that Covid loneliness increases anxiety while ASMR (audio-visual) tingling sensations help to reduce anxiety disorder.